PENGARUH DURASI BERMAIN PLAYSTATION TERHADAP PRESTASI BELAJAR PADA ANAK DI SD FRATER THAMRIN MAKASSAR - ASRIJAL BAKRI (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2019)
The habit of playing games can make children ignore homework and less reading. The excessive in playing game can interfere with daily life activities such as work, study, and other daily activities. If the game to control the behavior and daily life of a person, it can be said playstation has a negative effect (Wijayanti, 2009). This study aims to determine the influence playstation play on learning achievement in school-age children at SD. Frater Thamrin Makassar. The research design used is Observational Analytic research with Comparative Study approach that is by comparing two groups of independent variables that is long playstation play with which not long play of playstation. Duration of play determined according to standard measure that is less or more than 2 jam. Analisa bivariate done to see the influence between the independent variable of dependent variable by Mann Whitney Test. The results can be seen that the Mann-Whitney test obtained p value = 0.358 so that the value p> 0.005 and the value of Z hitung = 0.919 so that Z hitung < Z tabel (1.96) then the null hypothesis (Ho) is accepted and (Ha) rejected means no differences in learning achievement group Old and not long playstation play, it can be concluded that no influence playstation play time on the achievement of school-age children in SD. Frater Thamrin Makassar.